2017
DOI: 10.3892/ol.2017.7262
|View full text |Cite
|
Sign up to set email alerts
|

Combined acupuncture and general anesthesia on immune and cognitive function in elderly patients following subtotal gastrectomy for gastric cancer

Abstract: This study investigated the effects of acupuncture combined with general anesthesia on postoperative immune and cognitive functions in elderly patients undergoing subtotal gastrectomy. We recruited 96 elderly patients who received anesthesia for subtotal gastrectomy and randomly divided them into control (n=48) and experimental (n=48) groups. The control group received general anesthesia and the experimental group received combined acupuncture and general anesthesia. We measured hemodynamic immediately before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Hong et al reported that tailored psychological intervention could enable newly diagnosed GC patients to appropriately cope with the disease and improve their QoL (Hong, Wei, & Wang, 2015). The immune and cognitive functions in elderly GC patients might also be compromised following subtotal gastrectomy (Wang, Ou, & Qing, 2018). In addition, patients with GC were found with altered intrinsic brain activity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al reported that tailored psychological intervention could enable newly diagnosed GC patients to appropriately cope with the disease and improve their QoL (Hong, Wei, & Wang, 2015). The immune and cognitive functions in elderly GC patients might also be compromised following subtotal gastrectomy (Wang, Ou, & Qing, 2018). In addition, patients with GC were found with altered intrinsic brain activity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Combined use of above acuepoints can both ease pain and reduce cardiovascular stress. 8 In clinical general anesthesia, propofol is often used for sedation, and fentanyl is used for analgesia. The combination of propofol and fentanyl improves analgesia and sedation effects.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included. A flow diagram summarizing study outcomes is shown in Figure 1.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…The 16 studies that were included [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were all conducted in China and collectively enrolled a total of 1241 participants. All patients were over the age of 60 and underwent non-cardiac surgery under general anesthesia.…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
See 1 more Smart Citation